Bomarea rinconii (Alstroemeriaceae), a new species from the Talamanca Mountains in Chiriqui Province, Panama - González, Daniel Adolfo Cáceres (Phytotaxa, 2013)
Bomarea Mirbel (1804: 71; Alstroemeriaceae) includes 122 species (Govaerts 2013) and is divided into four subgenera (Hofreiter & Tillich 2002): Baccata (five species), Bomarea (ca. seventy species), Sphaerine(twelve species) and Wichuraea (eighteen species). Bomarea is distributed from Mexico and the Greater Antilles to southern South America (Gereau 1994). The centre of distribution of the genus is along the Andes from Colombia to Bolivia (Hofreiter 2008).